340 TELENURSING: MANAGEMENT OF LOOP RECORDER IMPLANTED IN PATIENTS WITH PREVIOUS CRYPTOGENETIC STROKE. (15th December 2022) - Morelli, Francesca
Abstract: Introduction: According to the latest studies, atrial fibrillation is associated with an increase in death of 1, 5 - 1, 9%. The main cause of this increase in mortality is ischemic stroke, secondary to detachment of emboliÂ starting from thrombus in the left atrium or in the left auricle. To date, the data indicate that the cause of stroke in the course atrial fibrillation is 14, 7% throughout Italy. The loop recorder is a small device that is implanted in the patientâ€™s subcutis through a minimally invasive procedure and allows you to go to record any arrhythmias. After implantation, it is fundamental to monitor and manage the device to recognize an arrhythmia, make a diagnosis and intervene promptly. One of the indications for the implantation of the loop recorder is precisely the presence of a previous cryptogenic stroke. Atrial fibrillation, being the cause of stroke, requires long - term monitoring to be diagnosed. In recent years there has been an increase in systems and modernization of this device which allows not only monitoring and diagnosis, but also timely intervention for a possible subsequent stroke episode. Purpose: The study that was conducted in the Hemodynamics Department of the Santa Maria Goretti Hospital in Latina analyzes the data related to the loop recorder system for cryptogenic stroke. The patients who have performed the implant are monitored, thanks to remote assistance, and after some time the atrial fibrillation is evaluated in how many of these patients. The final goal is therefore to evaluate the benefit of this preventive intervention. Materials and methods: There have been several researches that have made it possible to carry out the study on more than twenty patients. First, datas have been collected among all the people who implanted loop recorders, looking for the "previous cryptogenic strokeâ€as the reason for the implant. Once this type of patient was taken into consideration, real monitoring was carried out in the following months. Data collection and analysis were carried out on the database of Medtronic, Abbot and Biotronick which are the manufacturers of all devices that allow telemonitoring. Results: The study demonstrated the benefit of implanting this device, based on a precise diagnosis, which cannot be obtained in a short time. About 70% of the patients taken into consideration were diagnosed with atrial fibrillation and this made it possible to intervene in the most suitable way to prevent an eventual recurrence of stroke.